PERGESERAN SIKAP HAKIM PERADILAN AGAMA DI KOTA MEDAN DALAM PENETAPAN AHLI WARIS PENGGANTI SEBELUM DAN SESUDAH KHI - Abd. Mukhsin (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2011)
Abstract: This study examines the relationship between the introduction of the Compilation of Islamic Law (KHI) in 1991 and the shift of the attitudes Islamic court judges taking inheritance as a case in point. Prior to the introduction of KHI the judges are urged to refer to the classical works of Islamic jurisprudents in giving their judgment, the consequence of which gives the impression that there is no legal certainty in the decision of Islamic courts. The author argues that in post-introduction of KHI there has been a shift in the attitude of judges in determining biological status of an heir who had died prior to the predecessor. The author concludes that the emergence of the compilation has significant impact in improving the position of the Islamic court judges administratively, and that they were responsive to maintaining social equalities.Kata Kunci: KHI, sikap hakim, Peradilan Agama, ahli waris pengganti